Tinjauan Fiqh Jinayah terhadap Sistem Pembuktian Tindak Pidana Korupsi di Indonesia dan Malaysia - Fauzan Habibi Lubis; Noor Azizah; Lukman Hakim Harahap (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The crime of corruption manifests a pathological excretion of endemic crime and methodically destroys the foundations of state governance integrity and the teleological equilibrium of social justice holistically. The two jurisdictions between Indonesia and Malaysia are entangled in substantial epistemo-procedural complexity in the process of constructing evidence of corruption cases, crossing both from the positive legal dimension and the register of judicial ethics. This comparative study investigates the divergence and convergence trajectories that color the epistems of proof of corruption in both countries, with an analytical concentration focused on the doctrine of burden of proof inversion. By deploying a juridical-normative paradigm strengthened through comparative legal hermeneutics, the results of the study indicate that although Indonesia and Malaysia both implement a reversal mechanism of the burden of proof, the two countries exhibit striking heterogeneity in the procedural intensity and normative restrictions imposed. Malaysia prioritizes a balance between the effectiveness of institutional law enforcement and the prerogative of fundamental rights, while Indonesia shows a more aggressive vector in prosecuting disproportionately unexplained accumulated assets. Islamic criminal law strengthens the imperative of law enforcement through the postulates of substantive justice and the absolute prohibition of the practice of risywah. At its core, the effectiveness of proving corruption requires the availability of an architecturally adaptive legal system, a law enforcement apparatus with unparalleled integrity, and an ethical framework sublimated from the principles of universal justice.